They were her property : white women as slave owners in the American South - Jones-Rogers, Stephanie E. (2019)
"Bridging women's history, the history of the South, and African American history, this book makes a bold argument about the role of white women in American slavery. Historian Stephanie E. Jones-Rogers draws on a variety of sources to show that slave-owning women were sophisticated economic actors who directly engaged in and benefited from the South's slave market. Because women typically inherited more slaves than land, enslaved people were often their primary source of wealth. Not only did white women often refuse to cede ownership of their slaves to their husbands, they employed management techniques that were as effective and brutal as those used by slave-owning men. White women actively participated in the slave market, profited from it, and used it for economic and social empowerment. By examining the economically entangled lives of enslaved people and slave-owning women, Jones-Rogers presents a narrative that forces us to rethink the economics and social conventions of slaveholding America"--
Introduction: Mistresses of the market -- Mistresses in the making -- "I belong to de mistis" -- "Missus done her own bossing" -- "She thought she could find a better market" -- "Wet nurse for sale or hire" -- "That 'oman took delight in sellin' slaves" -- "Her slaves have been liberated and lost to her" -- "A most unprecedented robbery" -- Epilogue: Lost kindred, lost cause
Includes bibliographical references (pages 253-273) and index
Keywords: Slaveholders -- Southern States -- History; Slavery -- Southern States -- History; Women, White -- Southern States -- Social conditions -- 19th century; Slavery -- Economic aspects -- Southern States; Slaves -- Emancipation -- Southern States; African Americans -- Southern States -- Social conditions -- History -- 19th century; History